2012
DOI: 10.1155/2012/267327
|View full text |Cite
|
Sign up to set email alerts
|

Rumination and Age: Some Things Get Better

Abstract: Rumination has been defined as a mode of responding to distress that involves passively focusing one's attention on symptoms of distress without taking action. This dysfunctional response style intensifies depressed mood, impairs interpersonal problem solving, and leads to more pessimistic future perspectives and less social support. As most of these results were obtained from younger people, it remains unclear how age affects ruminative thinking. Three hundred members of the general public ranging in age from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 53 publications
6
63
1
1
Order By: Relevance
“…Including this function in our taxonomy of memory functions means that we are capturing those functions which are increasingly relevant for older adults. The positive nature of this class of functions is also consistent with other changes in autobiographical memory across the lifespan: older adults generally show a positivity bias in memory (Mather & Carstensen, 2005) and engage in less rumination (Sütterlin, Paap, Babic, Kübler & Vögele, 2012). Thus, our broader conceptualisation of autobiographical memory functions has more general applicability across the lifespan.…”
Section: Generative Functionsupporting
confidence: 74%
See 1 more Smart Citation
“…Including this function in our taxonomy of memory functions means that we are capturing those functions which are increasingly relevant for older adults. The positive nature of this class of functions is also consistent with other changes in autobiographical memory across the lifespan: older adults generally show a positivity bias in memory (Mather & Carstensen, 2005) and engage in less rumination (Sütterlin, Paap, Babic, Kübler & Vögele, 2012). Thus, our broader conceptualisation of autobiographical memory functions has more general applicability across the lifespan.…”
Section: Generative Functionsupporting
confidence: 74%
“…Thus we might expect that younger adults engage in more Reflective remembering than older adults, since reflection is associated with both constructive self-focused attention and with the self and directive functions of June , available online at: http://www.tandfonline.com/10.1080June /09658211.2013 autobiographical memory. Second, the autobiographical memories of older adults exhibit a positivity bias such that older adults remember more positive events and fewer negative events than do younger adults (Charles, Mather, & Carstensen, 2003;Kennedy, Mather, & Carstensen, 2004;Mather & Carstensen, 2005), and older adults engage in less rumination than younger adults (Sütterlin, Paap, Babic, Kübler & Vögele, 2012 Additional questionnaires (for a different study) were administered at the same time, and they are not reported here 5 . To study changes across the lifespan, we split our participant sample into agebased quartiles.…”
Section: Studymentioning
confidence: 99%
“…One possible reason is that adolescence represents a critical period with regard to depression due to several constructs, including the emergence of cognitive vulnerabilities (Abela & Hankin, 2008). Recent research suggests that certain cognitive processes, such as rumination, may be especially deleterious in adolescence (Sutterlin, Paap, Babic, Kubler, & Vogele, 2012). Thus, trauma history and lifetime mental health may be especially strong indicators of post-disaster depression symptomatology in adolescents because stressors associated with natural disasters may trigger negative cognitions about the past.…”
Section: Discussionmentioning
confidence: 99%
“…Several findings contributed to this idea. First, rumination prevents individuals from resolving their issues or their negative affect, and can be avoided by disengaging from the negative thoughts and focusing on the positive (Kessler & Staudinger, 2009; Sütterlin, Paap, Babic, Kübler & Vogele 2012; Torges, Stewart, & Nolen-Hoeksema, 2008). Second, older adults are more likely than younger adults to avoid rumination about especially negative experiences like the death of a loved one (Torges et al, 2008).…”
mentioning
confidence: 99%